Neurodegenerative disease: the medical imperative for the developed world - Hardy, John (Henry Stewart Talks, 2014)
Neurodegenerative disease: the medical imperative for the developed world, Neurodegeneration is a major health care crisis, Ages of neurodegenerative disease research, Clinicopathological description, Transmitter biochemistry, Genetic analysis of causation, Disease genes for all the major disorders, The future